Açúcar mascavo adicionado de açúcar bruto de alta polarização (Very High Polarization- VHP): uma avaliação tecnológica visando o desenvolvimento rural da agroindústria familiar - Andrade, Lucas de Almeida (2017)
In Brazil, brown sugar has only the value of polarization as a quality standard required by its own legislation, however, this value (90% polarization) does not represent the reality of the products found in the market. In addition, procedures such as the addition of high polarization (VHP) raw sugar have become frequent since this action can alter the final quality of the product and its processing. It is essential to develop new quality standards to be required for brown sugar, therefore, the quality of brown sugar produced without and with addition of VHP, both without and with pH correction, was evaluated in order to provide subsidies The results obtained show that there was no interaction between the raw material (cane juice with different contents of initial soluble solids) and the process used (addition of VHP with and without pH correction) for the variables used, except for the humidity variable, where the process of addition of VHP sugar accompanied by pH correction was able to influence and modify the raw material, resulting in a product with lower moisture content. Even though there is no such interaction, it should be noted that a new legislation should be drafted on the quality characteristics that brown sugar must have, thus creating a quality and identity standard that can benefit family producers.